Edgar & Ellen. Trick or twins [videorecording (DVD)]. (Lions Gate Entertainment, 2006)
Includes two specials. Trick or Twins - Edgar and Ellen are having a costume party and they are inviting you to come. Cold Medalist - the twins must team up with some unlikely allies if they want to win some medals.